Time-resolved photoemission from image-potential states - Fauster, Thomas; Weinelt, Martin (Journal of Electron Spectroscopy and Related Phenomena, 2001)
Electrons attracted by the image force to a metal surface are loosely bound and form a Rydberg-like series of states converging towards the vacuum level. Energies and lineshapes of these image-potential states are studied by two-photon photoelectron spectroscopy. The use of Ti-sapphire lasers as light sources has raised the count rates by several orders of magnitude and provided the opportunity to study the lifetime in the femtosecond range. Coherent excitation of several higher image-potential states of the Rydberg-like series leads to the observation of quantum beats in the time domain. The decay of the beat pattern and the lifetime are strongly influenced by adsorbates. The dependence on the quantum number of the image-potential states and the adsorbate will be discussed. The model system of image-potential states can be studied extremely well in present experiments and the results contribute to the understanding of photochemical processes and hot-electron dynamics at surfaces. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: two-photon photoemission; image-potential states; femtosecond dynamics